Adaptasi Kebijakan, Dampak Perkuliahan Daring, dan Strategi Mahasiswa Menjaga Imunitas Tubuh di Masa Pandemi Covid-19 - Karmila Kadir; Nurul Ilmi Idrus (Emik, 2021)
The world was shocked by a disaster in the form of a very dangerous virus, namely the corona virus or called Covid-19 which requires humans to be able to adapt to this Covid-19 pandemic situation, including in the field of education. At the higher educational level, the learning system changes from face-to-face learning to online learning. This article discusses how students adapt in relation to various policies, the impact of online learning, and students’ strategies in maintaining body immunity during the Covid-19 pandemic. Using a qualitative approach, this research was conducted in the city of Makassar, South Sulawesi Province. Data was collected using in-depth interview and observation. Those who participated in this study were 20 students, consisting of 15 males and five females, whose age ranging between 19 and 22 years. They come from various public and private campuses in the city of Makassar. The results of the study show that during the Covid-19 pandemic, students experienced many changes. Students themselves adapted to various emerging policies related to Covid-19, which include not only government and lecturing policies, but also internal student organization policies. For students, online lectures have impacted not only on the learning process, but also on student health. Various strategies were carried out by students in an effort to maintain body immunity in the midst of the Covid-19 pandemic policy, namely complying with health protocols; implementing a healthy lifestyle; managing stress; and taking supplements. It is argued in this articles that in order to prevent the spread of Covid-19, students adapt to the conditions that occur during the Covid-19 pendemic and apply related strategie. Lecturers also need to create a friendly environment and creative method of teaching, so that students can enjoy online learning on that limited screen.